Marine bacteria associated with the green seaweed Ulva sp. for the production of polyhydroxyalkanoates. (May 2021) - Gnaim, Rima; Polikovsky, Mark; Unis, Razan; Sheviryov, Julia; Gozin, Michael; Golberg, Alexander
Highlights: Exploring Polyhydroxyalkanoats production by green seaweed associative bacteria. Ulva sp. hydrolysates as a substrate for PHA production by microbial isolates. New Cobetia isolates afforded high PHA production, 61% (w/w) Abstract: This work aimed to isolate a series of bacterial strains associated with the green seaweed Ulva sp. and evaluate their capability to manufacture PHA. The effect of the type of supplemented sugars found to be in macroalgae, on the growth and PHA productivity of the strains was studied. Analysis of the 16S rRNA gene sequence of the isolated strains revealed that the PHA-producing bacteria were phylogenetically related to the genus Cobetia, Bacillus, Pseudoaltermonas and Sulfitobacter, which showed high PHA contents among the isolates. The highest PHA content was observed in the case of Cobetia strain, with up to 61% w/w in the presence of mannitol and 12% w/w on Ulva sp. acid hydrolysate as a substrate.